2021
DOI: 10.3390/en14051510
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Survival/Hazard Rate of Natural Ester Treated with Al2O3 Nanoparticle for Power Transformer Liquid Dielectric

Abstract: Increasing usage of petroleum-based insulating oils in electrical apparatus has led to increase in pollution and, at the same time, the oils adversely affect the life of electrical apparatus. This increases the demand of Mineral Oil (MO), which is on the verge of extinction and leads to conducting tests on natural esters. This work discusses dielectric endurance of Marula Oil (MRO), a natural ester modified using Conductive Nano Particle (CNP) to replace petroleum-based dielectric oils for power transformer ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…PKO. In other studies, for instance, Raj et al (2021) reported the excellent performance of marula oil blended with Al 2 O 3 by showing up to 64.00% on its breakdown voltage (BDV) enhancement, and Duzkaya and Beroual (2021) reported the increment of AC BDV of FR3 blended with ZnO at 0.1 to 0.3 g L -1 concentrations. On the other hand, some types of NPs do not constantly improve the dielectric strength of NEOs, which others have also reported.…”
Section: P R E S Smentioning
confidence: 94%
See 1 more Smart Citation
“…PKO. In other studies, for instance, Raj et al (2021) reported the excellent performance of marula oil blended with Al 2 O 3 by showing up to 64.00% on its breakdown voltage (BDV) enhancement, and Duzkaya and Beroual (2021) reported the increment of AC BDV of FR3 blended with ZnO at 0.1 to 0.3 g L -1 concentrations. On the other hand, some types of NPs do not constantly improve the dielectric strength of NEOs, which others have also reported.…”
Section: P R E S Smentioning
confidence: 94%
“…Several plant oils, such as palm oil, pongamia pinnata oil, olive oil, marula oil, coconut oil, etc., have been used as the raw materials. Their potential suitability as transformer oils has been investigated and examined thoroughly by many researchers (Ariffin et al, 2017;Baruah et al, 2019;Farade et al, 2020;Genga Devi et al, 2016;Koutras et al, 2020a;Samikannu et al, 2021). Researchers eventually realised that VO-based liquid insulation needed various modifications to overcome its shortcomings and be employed as the insulating liquid in transformers (Moosasait and Maria Siluvairaj, 2021).…”
Section: P R E S Smentioning
confidence: 99%
“…Any slight change in the breakdown strength of the liquid insulation deteriorates enforce stress on the solid insulation [3]. The breakdown strength is mainly affected by adding water content to the oil or generating polar compounds due to an ionization reaction [4]. This leads to the weakening of the insulation capabilities of solid insulation.…”
Section: Introductionmentioning
confidence: 99%
“…The subject of natural ester liquids is continued in the papers [5] and [6]. The first one presents the results of the studies on the electrical behavior of natural ester-based ZnO nanofluids at different concentrations in the range of 0.05-0.4 g/L.…”
mentioning
confidence: 99%
“…The authors also conclude that increasing nanoparticles concentration beyond the value of 0.4 g/L reveals the implication of a tunnelling/bridging mechanism that may reduce the value of AC breakdown voltage. In turn, the authors of [6] analyzed the natural ester (Marula Oil) treated with Al 2 O 3 with concentrations varying from 0.1 g/L to 2 g/L and 0.25 g/L. They use mathematical considerations to determine survival and hazard rate.…”
mentioning
confidence: 99%